OPTIMIZATION OF THEAFLAVIN EXTRACTION PROCESS FROM TEA LEAF FERMENTATION METHOD WITH UV LIGHT EMISSION - Muhammad Makhdum Ibrahim (Sekolah Vokasi Universitas Diponegoro, 2021)
[Title: Optimization of Theaflavin Extraction Process from Tea Leaf Fermentation Method With UV Light Emission]. Theaflavins are the results obtained in experiments with theaflavin variables with UV light, with an extraction time of 20 minutes at a temperature of 23,786 oC the theaflavin content obtained is 0.703 %, while for extraction with a time of 35 minutes 45 oC the theaflavin content is 0.939 %, and extraction with a time of 63,284 with 66,213 oC minutes obtained theaflavin content of 0.336%, at the time of extraction time of 63,284 minutes there was a decrease, this is because the longer fermentation time causes changes in theaflavin bioactive compounds into bioactive compounds thearubigin. These results indicate that UV light has a significant